2023
DOI: 10.1002/adma.202300441
|View full text |Cite
|
Sign up to set email alerts
|

Move Aside Pentacene: Diazapentacene‐Doped para‐Terphenyl, a Zero‐Field Room‐Temperature Maser with Strong Coupling for Cavity Quantum Electrodynamics

Abstract: quality-factor (Q) microwave resonator magnetically loaded with optically pumped pentacene doped in para-terphenyl (Pc:PTP) provides one route toward this goal, [1] and diamond with negatively charged nitrogen-vacancy defects (NV − diamond) has also been considered. [2] However, attaining a sufficiently high spin polarization density for strong coupling from other materials has, at room-temperature, proven elusive.Room-temperature masers (microwave amplification by stimulated emission of radiation) can be made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…No characteristic emission peaks of doping molecules (PNZ, DHPNZ, and DAT) were observed in PNZ-PTP, DHPNZ-PTP, and DAT-PTP crystals, indicating that PNZ, DHPNZ, and DAT were mixed with only p -terphenyl and were not successfully doped into the p -terphenyl lattice. According to previously reported experimental results, DAP was doped into the p -terphenyl lattice, replacing one of the p -terphenyl molecules . The possible replacement process can be seen in Figure .…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…No characteristic emission peaks of doping molecules (PNZ, DHPNZ, and DAT) were observed in PNZ-PTP, DHPNZ-PTP, and DAT-PTP crystals, indicating that PNZ, DHPNZ, and DAT were mixed with only p -terphenyl and were not successfully doped into the p -terphenyl lattice. According to previously reported experimental results, DAP was doped into the p -terphenyl lattice, replacing one of the p -terphenyl molecules . The possible replacement process can be seen in Figure .…”
Section: Methodsmentioning
confidence: 94%
“…previously reported experimental results, DAP was doped into the pterphenyl lattice, replacing one of the p-terphenyl molecules. 47 The possible replacement process can be seen in Figure 3. In order to characterize crystal crystallinity and analyze crystal composition, XRD patterns of pure p-terphenyl and doped crystals are shown in Figure 4a,d.…”
Section: Growth Of Nitrogenous Biphenyl-doped P-terphenylmentioning
confidence: 99%
“…The energy difference (Δ E ST ) between the first excited singlet state (S 1 ) and the most energetically proximal triplet state (T 2 ) was used to predict the ISC rates (κ ISC ) . Subsequent ab initio investigations revealed that guest–host interactions significantly impact the relative energies of neighboring singlet and triplet states, exemplifying some of the inherent difficulty in computationally predicting maser materials. , Nevertheless, these studies informed the discovery of 6,13-diazapentacene-doped p -terphenyl ( DAP :PTP) as an alternative maser gain media operating with a 620 nm pulsed laser . The discovery of new maser candidates is also hindered by reliance on doped crystalline materials such as p -terphenyl.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 Nevertheless, these studies informed the discovery of 6,13-diazapentacene-doped p -terphenyl ( DAP :PTP) as an alternative maser gain media operating with a 620 nm pulsed laser. 13 The discovery of new maser candidates is also hindered by reliance on doped crystalline materials such as p -terphenyl. Crystalline hosts are highly selective toward their compatible dopants which limits the number of candidates that can be readily explored.…”
Section: Introductionmentioning
confidence: 99%
“…This produced a burst of maser emission that lasted for 350 µs. The maser resulted in a peak microwave power output of -10 dBm, 10 8 times higher than the hydrogen maser, with an optical pump threshold power of around 230 W. There have been subsequent reports of room-temperature masing using pentacene [5][6][7] and similar media [8] pumped by a pulsed optical parametric oscillator in the range 570 -620 nm, itself pumped by a frequency doubled pulsed neodymium-doped yttrium aluminum garnet (Nd:YAG) laser. A room-temperature maser was also demonstrated using an ensemble of nitrogen-vacancy centres in diamond [9].…”
mentioning
confidence: 99%